Analysis Determination Of Shortest Route Delivery Using Dijkstra Algorithm - Lestari S A; Puspa A K (Bandar Lampung University (UBL), 2017)
Over the rapid technological developments in the field of business especially now a lot of companies that create delivery services goods. With various bustle owned, service users delivery of goods more want something practical, fast, and economical especially for local communities urban areas. In perform delivery services goods main concern is the time and cost efficiency, by sending goods via freight, of course we expect the optimal route in order to arrive on time and do not takes a lot of travel expenses such as gasoline. The shortest route problem is a classic problem often encountered in daily life in various sectors of life, including in the field of transportation. This problem becomes an important issue because it deals with the problem minimizing the cost and time required efficiency. Shortest path is the search for the shortest route or path between nodes that exist in graph. Cost generated is minimum. the shortest path is one problem that can be solved by using graph. if given a weighted graph, the shortest path problem is how do we seek a path in the graph that minimizes the weighted sum forming the side of the track. (arix oyouz: 2013). Transport is one of the most important part in our daily lives that will enable us to reach the place of destination faster and eficient. Transport users in his journey would require so much faster shortest path to the place of destination and it takes a lot of time and transport costs